An Analysis of Controlled Waterfowl Hunting and Hunter Characteristics at Wisconsin's Sandhill Wildlife Demonstration Area (1963 through 1971) - Meier, William S. (University of Wisconsin-Stevens Point, 1973)
A study of controlled waterfowl hunting was conducted at Wisconsin's Sandhill Wildlife Demonstration Area from the fall of 1963 through that of 1971• a hunter characteristics survey was added in 1971. Mallards and Canada geese were the birds most frequently killed at Sandhill during the 9-year study; 1967 was the most successful year. Units D and G were the most heavily hunted waterfowl hunting units, most of the birds crippled were crippled in units D and G, and successful hunters spent more time in units D and G than did the unsuccessful hunters. Successful hunters hunted an average of 5.8 hours per trip while the unsuccessful hunters hunted an average of 4.2 hours per trip. An average of 10.3 hours of hunting were required to harvest each bird. Dogs were used on only 14 percent of the hunting trips from 1963 through 1969. Successful hunters who used dogs averaged 1.7 birds per trip while those who did not averaged 1.6 birds. Dog users had a crippling rate of 20 percent and non-dog users had one of 21 percent. It was also found that as the years of a hunter's hunting experience increased, the amount of time he spent hunting and the amount of waterfowl he killed increased, while his c1:ppling losses decreased. Hunters using decoys or a combination of hunting techniques were by far the most successful, but passshooters had the lowest crippling rate. Most of the hunter trips to Sandhill were made from distances of either less-than 50 miles or greaterthan 100 miles, with a relatively small portion of trips made from the intermediate distance of 50 to 100 miles. The greatest percentage of trips (53 percent) were made from Wood County (the county in which Sandhill is located). The majority of hunters questioned in the hunter characteristics survey approved of the regulated system of hunting at Sandhill, thought that the system gave everyone an equal hunting opportunity, and were in favor of the Sandhill system of regulated hunting being initiated on other public waterfowl hunting areas in Wisconsin. The majority of hunters also were primarily urban dwellers with an appreciation for wildlife and the esthetic values of nature. Most hunters had an annual income of $7,000 or more, did not belong to a sportsmans organization, read more than one outdoor magazine; but did not read the Wisconsin Conservation Bulletin, and have never read a book on wildlife management. Hunters also did not give strong support to the selective shooting policy for waterfowl.